Managing Entitlement inside the Classroom: Policies and Approaches (International Journal of Innovative Research in Engineering & Management, 2022)
In academics, student entitlement refers to  the propensity to have high expectations of academic  achievement without accepting personal responsibility for  attaining that accomplishment. Even if they are not typical  of all students, those who show a feeling of entitlement place  a significant demand on the time and energy of their teachers.  We look at student rights in its cultural context, focusing on  the consumer mentality's dominance, academic standards,  and the contemporary student population's self-esteem. With  that, we'll go thru the a few different approaches to dealing  with arrogant behaviour. More clarity in norms and  evaluation, as well as precise norms regulating teacher student relationships and larger efforts to re-socialize  children and staff, we think, would help, would aid in the  prevention of these types of incidents.
Keywords: Assignments; Faculty; Grade; Institution; Student Entitlement